(untitled) (Journal of Atomic and Molecular Sciences, 2014)
The mechanism of the cyclic reaction CO(C_∞ v, ^1^+) + N_2O(C_∞ v, ^1^+) → N_2 (D_∞ h, ^1^+_g)+ CO_2(D_∞ h,^1^+_g) catalyzed by Ni^+ has been investigated on both double and quartet potential energy surfaces (PESs). The reactions were studied by the UB3LYP density functional theory. The calculated results of different spin PES show that the reaction proceeds in a two-step manner and spin crossing between different PES occurs. The involved crossing between the PES has been discussed by means of the intrinsic reaction coordinate approach used by Yoshizawa et al., and the crossing points were located. Furthermore, the spin-orbit coupling (SOC) is calculated between electronic states of different multiplicities at the crossing points to estimate the intersystem crossing probabilities.